THE EFFECTIVENESS OF COMPREHENSIBLE INPUT AND INCOMPREHENSIBLE INPUT FOR ENHANCING ENGLISH SPEAKING SKILL OF RECOUNT TEXT ON MALE AND FEMALE STUDENTS - Fabianto, Eko; Hartono, Rudi (English Education Journal, 2015)
This study investigates the effectiveness of Comprehensible Input and Incomprehensible Input for enhancing English speaking skill of recount text related to gender difference. This studyis a quantitative in nature, using an experimental factorial design 2x2. The participants of this study were 129students of the tenth gradersof Computer-Networking Department at State Vocational School 1 Slawi.Thestudents were divided into two groups, experimental group1 and experimental group2. Each group consisted of 2 classes. The students of experimental group1 were given Comprehensible Input in learning speaking skill of recount text and the experimental group2 were given Incomprehensible Input in learning speaking skill of recount text.This study used random sampling as its sampling technique.The findings of this study show that both comprehensible input and incomprehensible input have significant effect for enhancing speaking skill of recount text regardless of the gender. However, input given for enhancing thespeaking skill and studentâs gender do not have any interactions.